Empowerment of Zakat, Infaq, Alms, and Waqf (Ziswaf) Mosques in Banjarmasin: from Historical Mosques to Sectoral Mosques - Ishom, Muhammad; Fatmawati, Fatmawati; Miftah, Ahmad Harisul (Fakultas Syariah UIN Sultan Maulana Hasanuddin Banten, 2023)
This study aims to describe and analyze the empowerment of zakat, infaq, alms and waqf (ZISWAF) mosques in Banjarmasin. The research data is classified according to the categorization of mosques, where one with another has different functions and user communities (congregations) so that they are different in terms of income and management of Ziswa. The mosques that were the object of research were (a) Sultan Suriansyah Mosque; (b) Jami Sungai Jingah Mosque; and (c) Sabilal Muhtadin Grand Mosque. With a descriptive approach, in general, the collection of Ziswaf in each mosque is different in ways and strategies, but generally the empowerment of Ziswaf is stronger for the benefit of worship than economic empowerment and social piety.